Epithelial Microvesicles Promote an Inflammatory Phenotype in Fibroblasts. (June 2016) - Bi, J.; Koivisto, L.; Owen, G.; Huang, P.; Wang, Z.; Shen, Y.; Bi, L.; Rokka, A.; Haapasalo, M.; Heino, J.; Häkkinen, L.; Larjava, H.S.
Microvesicles (MVs) are extracellular vesicles secreted by various cell types that are involved in intercellular communication. We hypothesized that in human periodontal disease, the pocket epithelium releases MVs, which then modulate gene expression in the underlying fibroblasts to control periodontal inflammation. MVs were isolated from culture medium of gingival epithelial cells (GECs) treated with oral bacterial biofilm extract or left untreated. Biofilm treatment significantly increased MV release from the GECs. Mass spectrometry of GEC-MVs identified a total of 2, 173 proteins, of which about 80% were detected in MVs from both control and biofilm-treated GECs. Among 80 signature genes of human gingival fibroblasts, 20 were significantly regulated ( P < 0.05) by MVs from control and biofilm-treated GECs in a similar manner. Matrix metalloproteinase 1 and 3 and interleukin 6 and 8 showed the strongest regulation at the mRNA and protein levels. Several cellular signaling pathways were activated by GEC-MVs in human gingival fibroblasts, including Smad and mitogen-activated protein kinase–associated pathways ERK1/2, JNK, and p38. However, ERK1/2 signaling dominated in the MV-induced gene expression changes. The results demonstrate that GEC-MVs have a strong regulatory effect on the expression of fibroblast genes associated with inflammation and matrix degradation and that bacterial biofilm stimulates the generation of GEC-MVs. This suggests that bacterial biofilms can contribute to the initiation and progression of periodontal disease by promoting a tissue-destructive phenotype in gingival fibroblasts via the enhanced secretion of epithelial MVs.